Investigating the Influence of Stacking Sequences on the Physical and Mechanical Characteristics of Coconut Coir Fiber-Reinforced Unsaturated Polyester Composites - Asyraf M.R.M.; Syamsir A.; Supian A.B.M.; Zaki M.A.F.M.; Hazrati K.Z.; Ashraf W.; Anggraini V.; Madenci E.; zk?l? Y.O.; Aksoylu C. (Korean Fiber Society, 2025)
The coconut fruit is cultivated for fruit in tropical countries, whereas its husk and shell are a potential source of natural fiber, which is mostly disposed of as waste material. There is an increasing trend in research and innovation to replace synthetic fiber with natural fiber to reduce the environmental carbon footprint. However, using natural fiber in polymer composite is challenging because of the lower mechanical strength and hydrophilic nature of the natural fiber. The literature reported on mechanical and moisture resistance properties of coir fiber polymer composite with different fiber orientations is very limited. Thus, this research aims to evaluate the mechanical properties (flexural and impact) and moisture resistance properties of the coir fiber reinforced composite. The fiber ware stacked with three different fiber orientations, namely 0/0/0, 0/90/0 and 0/+ 45/0. The composite was fabricated with the hand lay-up technique. The overall results indicated that the composite specimens with the orientation of 0/0/0 indicated the best flexural properties and water penetration resistance in the composite. The stacking sequence of 0/ + 45/0 gave the best impact properties. However, at this orientation, it gave the lowest water resistance among the studied configurations. ? 2024, The Author(s), under exclusive licence to the Korean Fiber Society.